(untitled) (International Journal of Food and Nutritional Sciences, 2022)
"AI Horizon: Illuminating the Future of Marketing, Consumer Behavior, and Psychology" is a groundbreaking exploration into the transformative role of artificial intelligence in shaping the landscape of marketing, understanding consumer behavior, and advancing the field of psychology. As we stand at the intersection of technology and human psychology, this book delves into the profound impact that AI is having on these interconnected domains, offering a visionary glimpse into what lies ahead. In an era where AI has evolved from being a mere buzzword to a powerful tool that businesses, researchers, and psychologists can harness, this book serves as a beacon, guiding readers through the vast possibilities and potential challenges of this AI-driven future. From personalized marketing strategies that leverage AI’s predictive capabilities to the ethical considerations surrounding data privacy and psychological profiling, "AI Horizon" navigates the complex terrain of AI’s convergence with marketing and psychology. Readers will embark on a journey through the latest AI-driven innovations, exploring how machine learning, natural language processing, and neural networks are revolutionizing advertising, customer engagement, and market research. Additionally, the book delves into the ways in which AI is reshaping our understanding of human behavior, shedding light on the intricate workings of the mind through advanced data analytics and psychological insights. With expert perspectives, real-world case studies, and thought-provoking discussions, "AI Horizon" equips readers with the knowledge they need to navigate the evolving AI landscape. Whether you are a marketing professional seeking to harness the power of AI, a researcher exploring the frontiers of consumer behavior, or a psychologist interested in the evolving field of AI psychology, this book offers an illuminating glimpse into the exciting future where AI and human expertise converge to reshape our world.